Reduction of Intracellular-Reactive Oxygen Species and Diminished Mitogen-Activated Protein Kinases (MAPKs) Activation are Associated with Oral Squamous Cell Carcinoma Cell Aggressiveness - UTAIPAN, Tanyarath; SATTAYAKHOM, Apsorn; PRACHONGSAI, Issara; CHARONG, Nurdina; CHUNGLOK, Warangkana (Walailak Journal of Science and Technology (WJST), 2017)
Oral squamous cell carcinoma (OSCC) is a serious health problem in many countries. Several drugs have been used to treat head and neck and oral cavity cancers. However, the success rate has not been impressive because of the heterogeneity of cancerous cells, resulting in differential responsiveness to chemotherapy. Two distinct phenotypes of OSCC cells, the CLS-354/WT and CLS-354/DXcells, have been used as in vitro cell models for this study. CLS-354/DXcells were more aggressive than CLS-354/WTcells, supported by the observation that CLS-354/DXcells can undergo epithelial-mesenchymal transition (EMT), grow anchorage-independently, and increase invasiveness. We investigated the preliminary redox status of these 2 cell lines, including levels of reactive oxygen species (ROS) and cellular antioxidants, using flow cytometry analysis and ABTS+ free radical scavenging assay, respectively. A 7-fold decrease in ROS level was detected in CLS-354/DXcells, comparing with CLS-354/WTcells, while antioxidant capacity was not different from that of CLS-354/WT cells. Hydrogen peroxide, a ROS modulating agent, could induce ROS levels, and caused cell death in CLS-354/WT greater than that of CLS-354/DX cells. Of note, hydrogen peroxide-induced cytotoxicity could be rescued by N-acetyl cysteine, confirming ROS-mediated cytotoxicity in both cell lines. ROS-sensitive mitogen-activated protein kinases (MAPKs) were observed using immunoblot assay. The expressions of p-JNK1/2 and p-p38 MAPK in CLS-354/DX cells were absent, while these expressions were abundantly detected in CLS-354/WTcells. This suggests that lower ROS levels, with the concomitant reduction of JNK and p38 MAPK activation in CLS-354/DX cells, are associated with cancer cell aggressiveness. These findings provide significant evidence of the resistance to ROS-modulating agents in aggressive OSCC cells.